Interaction of Epididymal Epithelia and their Secretions with Spermatozoa Supports Functional and Morphological Changes During Long-Term Storage in the Chinese Soft-Shelled Turtle (Pelodiscus sinensis). (June 2020) - Tarique, Imran; Tariq, Mansoor; Bai, Xuebing; Wenjia, Qu; Yang, Ping; Huang, Yufei; Sheng, Yang; Vistro, Waseem Ali; Chen, Quisheng
Abstract: Post-testicular maturation of spermatozoa is crucial for attaining the morphological and functional capabilities needed for successful fertilization. Epididymal epithelia offer a favorable environment for spermatozoa that are stored long term in the turtle epididymis; however, sperm–epithelial interactions during storage, which are enormously important for sperm functional and morphological maturation, are still largely unknown in turtles. The present study examined the epididymis during the sperm-storage period (November–April) in the Chinese soft-shelled turtle ( Pelodiscus sinensis ). Light and transmission electron microscopy were used to determine the cellular features of each epididymal segment (caput, corpus, and cauda) and their epithelial interactions with the spermatozoa. Spermatozoa were mainly located in the lumena of caput, corpus, and cauda epididymides. Numerous spermatozoa were bound to apical surfaces of the epithelia, and several were even embedded in the epithelial cytoplasm of the caput and corpus epididymides. No embedded spermatozoa were found in the cauda epididymis. In all epididymal segments, principal and clear cells showed the synthetic activity, evidenced by a well-developed endoplasmic reticulum network and high and low electron-dense secretory materials, respectively. Principal and clear cells in the caput and corpus segments showed embedded spermatozoa in electron-dense secretions and in the lipid droplets within the cytoplasm. No lysosomes were observed around the embedded spermatozoa. The lumena of the caput and corpus segments showed few apocrine and low electron density secretions. In the lumen of the cauda epididymidis, different secretions, such as holocrine with low and high electron density and their fragmentation, apocrine, and dictyosome, were found and are summarized. Altogether, sperm physical interactions with secretions either in the cytoplasm of epithelium or in the lumen may support the viability, morphological maintenance, and transfer of various proteins involved in long-term sperm storage in the turtle. This interaction could help us to understand the mechanisms of long-term sperm storage and provide more insights into the reproductive strategies of turtle sperm preservation.